Pt-Ga Model SCALMS on Modified HOPG: Thermal Behavior and Stability in UHV and under Near-Ambient Conditions - Hohner, Chantal; Kettner, Miroslav; Stumm, Corinna; Blaumeiser, Dominik; Wittkämper, Haiko; Grabau, Mathias; Schwarz, Matthias; Schuschke, Christian; Lykhach, Yaroslava; Papp, Christian; Steinrück, Hans-Peter; Libuda, Jörg (Journal of Physical Chemistry C, 2020)
We have prepared model systems for Pt-Ga supported catalytically active liquid metal solutions (SCALMS) by physical vapor deposition of Pt and Ga onto highly oriented pyrolytic graphite (HOPG). Prior to metal deposition, the HOPG support was modified by Ar+ bombardment. In this work, we focus on the stability of the Pt-Ga deposits toward agglomeration, which is a critical challenge in application. Specifically, we study the behavior of the model catalysts in ultrahigh vacuum (UHV) and under near ambient pressure (NAP) conditions at different temperatures. We use CO as a probe molecule to examine changes in the surface composition of the Pt-Ga deposits by in situ infrared reflection absorption spectroscopy (IRAS). In specific, we combine IRAS and ex situ atomic force microscopy (AFM) to study changes induced by annealing. We find that sintering effects are strongly dependent on the thickness of the deposited Pt-Ga layers. Our data suggest that particle ripening leads to a separation of the system into disperse Pt-rich and large Ga-rich particles. In the NAP regime, we performed simultaneous measurements with polarization modulation IRAS (PM-IRAS) and near ambient pressure X-ray photoelectron spectroscopy (NAP-XPS). The alloying of Pt and Ga is accompanied by a shift of Pt 4f and Ga 3d photoelectron lines to higher binding energies. Although partial oxidation of Ga is observed upon CO exposure at pressures in the millibar regime, PM-IRAS shows'adsorbed CO at a frequency typical for Pt ensembles in a Ga matrix.
CRIS-Team WoS Importer:2020-02-18